1998
DOI: 10.1111/1469-7610.00373
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Distribution of Spontaneous Attention Shifts between Social and Nonsocial Stimuli in Autistic, Typically Developing, and Nonautistic Developmentally Delayed Infants

Abstract: Spontaneous shifts of attention were observed in autistic, typically developing, and nonautistic developmentally delayed infants. Three types of attention shifting behaviour were observed; (1) between an object and another object, (2) between an object and a person, and (3) between a person and another person. The two control groups shifted attention more frequently between an object and a person than between an object and another object or between a person and another person. The infants with autism showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
153
3
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(172 citation statements)
references
References 25 publications
11
153
3
5
Order By: Relevance
“…For example, it has been shown that while processing of non-human stimuli such as objects is normal, attending to and processing human stimuli appears abnormal in autistic individuals (Behrmann et al 2006;Bird et al 2006;Boucher and Lewis 1992;Dawson et al 1998;Klin et al 2009;Swettenham et al 1998). In addition, Spengler et al (2010) recently observed that autistic adults showed impaired top-down inhibition of automatic imitation in response to finger movements, highlighting that altered regulation of imitation may lead to imitation impairments in autistic people.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that while processing of non-human stimuli such as objects is normal, attending to and processing human stimuli appears abnormal in autistic individuals (Behrmann et al 2006;Bird et al 2006;Boucher and Lewis 1992;Dawson et al 1998;Klin et al 2009;Swettenham et al 1998). In addition, Spengler et al (2010) recently observed that autistic adults showed impaired top-down inhibition of automatic imitation in response to finger movements, highlighting that altered regulation of imitation may lead to imitation impairments in autistic people.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps one of the most striking features, though, is that toddlers and young children with ASD tend not to look towards other people as much as typically developing children do. Swettenham et al (1998) found that during free play, 18-20 month old toddlers, later diagnosed with ASD, spent less time looking at people and displayed fewer gaze shifts between objects and people than typically developing children and children with developmental delay. In retrospective studies of home video-tapes of first birthday parties, it was found that children later diagnosed with ASD looked less at other people than typically developing children (Osterling and Dawson 1994).…”
mentioning
confidence: 93%
“…Children with autism may also not find others' facial expressions intrinsically rewarding. Certainly, there is evidence of reduced attention to faces and to looking at eyes in particular (Swettenham et al 1998). This reduced interest in faces is likely to impair their face processing skills, so that children with ASC do not become 'face experts' like their typically developing peers (Dawson et al 2005).…”
mentioning
confidence: 99%